The Influence of Motivation on the Achievement Index of Early Level Dental Health Vocational Program Students During the Pandemic - Pudentiana Rr. R. E.; Ngatemi; Yusuf K.; Indrayati F.; Fakhrunnisa (Global Writing Academica Researching and Publishing, 2024)
Motivation is a process that instigates change within an individual, empowering them to act towards achieving specific goals. Individuals with strong achievement motivation strive to be intelligent and enhance or refine their abilities to fulfill their tasks. This study aims to explore the motivation and achievement index of Level I students majoring in dental nursing at Poltekkes, Ministry of Health, Jakarta I, in 2021. Utilizing a descriptive research design, the population for this study comprised 39 Level I students, all of whom were included in the sample through a total sampling technique. Data were collected via a questionnaire administered through a Google Form. The findings reveal that the majority of students' learning motivation falls within the high category, involving 21 respondents (53.8%). Regarding the student achievement index, the majority, or 35 respondents (89.7%), were categorized within the good learning achievement bracket. The study further indicates that females predominantly exhibit good motivation, accounting for 19 respondents (48.7%). Research on the achievement index based on gender demonstrates that both genders show a high motivation level, with 3 male respondents (7.7%) and 32 female respondents (82.1%) respectively. The study also highlights that students with high learning motivation paired with a good achievement index total of 20 respondents (51.2%), with no students having high motivation alongside a merely sufficient performance index. In conclusion, Level I students of the Department of Dental Nursing at Poltekkes, Ministry of Health Jakarta I, predominantly exhibit high motivation and good learning achievement indexes, with a significant majority being female.